2015
DOI: 10.1016/j.ophtha.2015.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Three Prophylactic Strategies to Prevent Clinical Macular Edema after Phacoemulsification Surgery

Abstract: PURPOSE To study the relationship of chemoprophylaxis and other factors on the occurrence of acute, clinical postoperative macular edema. DESIGN Retrospective cohort study. The drug regimens consisted of postoperative topical prednisolone acetate (PA) alone or with nonsteroidal anti-inflammatory drug (PA+NSAID) or intraoperative subconjunctival injection of 2 mg triamcinolone acetonide (TA) alone. PARTICIPANTS Patients undergoing phacoemulsification at Kaiser Permanente, Diablo Service Area, Northern Calif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 27 publications
0
54
0
6
Order By: Relevance
“…As with past studies, 3, 4 we excluded complex phacoemulsification cases and cases performed by glaucoma, oculoplastic or retinal specialists as well as procedures by any surgeon combined with corneal transplant (ICD-9 11.6, CPT4 codes 65710-65715) or glaucoma surgery (ICD-9 12.54, 12.64, 12.66, 12.69,-12.7, CPT4 codes 65850, 66170, 66172, 66180, 66185).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As with past studies, 3, 4 we excluded complex phacoemulsification cases and cases performed by glaucoma, oculoplastic or retinal specialists as well as procedures by any surgeon combined with corneal transplant (ICD-9 11.6, CPT4 codes 65710-65715) or glaucoma surgery (ICD-9 12.54, 12.64, 12.66, 12.69,-12.7, CPT4 codes 65850, 66170, 66172, 66180, 66185).…”
Section: Methodsmentioning
confidence: 99%
“…We counted only one case of macular edema per patient because it was not possible based on coding alone to determine the laterality of the macular edema or whether the condition was unilateral or bilateral. To improve specificity, 4 we required macular edema cases to have undergone ocular coherence tomography and to have filled a prescription for ophthalmic prednisolone during the 120 days after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Another recent study that retrospectively reviewed more than 16 000 phacoemulsification surgeries by 17 surgeons defined clinical postoperative macular edema as a visual acuity of 20/40 or worse with confirmatory findings on OCT. 49 Compared with eyes that received prophylaxis with topical prednisolone alone, the eyes that were additionally treated with postoperative NSAIDs experienced a 55% reduction in the incidence of macular edema.…”
Section: Nonsteroidal Antiinflammatory Drugs and Cystoid Macular Edemamentioning
confidence: 99%
“…92 Recently, a comparative effectiveness retrospective study of over 4500 eyes that received generic diclofenac, flurbiprofen, or ketorolac revealed no corneal melts or other significant corneal events other than 1 instance of temporary mild corneal thinning in an eye treated with prednisolone alone in a patient with rheumatoid arthritis. 49 …”
Section: Adverse Effects Of Topical Nonsteroidal Antiinflammatory Drugsmentioning
confidence: 99%
“…Both potent and weaker corticosteroids were less effective than NSAIDs in reducing the risk of CME. In addition, a large retrospective cohort study found that adding an NSAID to postoperative topical prednisolone acetate was associated with a lower risk of clinical CME compared with prednisolone therapy alone (odds ratio 0.45; 95% confidence interval 0.21–0.95) 24. Clinical CME was defined as evidence of macular thickening on OCT and VA of 20/40 or worse, ascertained between 5 and 120 days after cataract surgery.…”
Section: Introductionmentioning
confidence: 99%